898 ROLE OF 3D ECHOCARDIOGRAPHY IN AORTIC VALVE ABNORMALITIES: TWO CASES REPORT. (15th December 2022) - Monaco, Maria Lo; Stankowski, Kamil; Oliva, Angelo; Figliozzi, Stefano; Fazzari, Fabio; Mantovani, Riccardo; Curzi, Mirko; Cannata, Francesco; Marconi, Manuel; Fumero, Andrea Davide; Stefanini, Giulio Giuseppe; Torracca, Lucia; et al.
Abstract: Introduction: Aortic valves with a number of cusps different from two or three are infrequent congenital anomalies that might manifest with valvular disease in young patients. We present two cases of unicuspid and quadricuspid aortic valve diagnosed in our Center. Clinical Cases: Case 1. A 23-year-old asymptomatic male was admitted to our Hospital because of the necessity of bone marrow transplantation for Hodgkin lymphoma. He had a previous diagnosis of bicuspid aortic valve and presented a 5/6 mid-systolic harsh murmur, heard best at the right upper sternal border and radiating to the neck. ECG showed sinus rhythm with left ventricular hypertrophy. BNP was in normal range (31 pg/ml). At trans-thoracic echocardiography, there was severe aortic stenosis [peak/mean gradient of 100/67 mmHg with an aortic valve area of 1.04 cm 2 (0.54 cm 2 /m 2 ); V max was 5 m/s] without regurgitation and dilation of the ascending aorta (39 mm), however the morphology of the aortic valve remained undefined. Left ventricle showed hypertrophy (maximum wall thickness = 13 mm) with normal volumes and systolic function. Thus, the patient underwent to 3D-Transesophageal echocardiography, which demonstrated unicuspid aortic valve with a lone commissure between L-NC and anterior calcification. After multidisciplinary discussion, the patient underwent close follow-up and aortic valve replacement was planned after the bone marrow transplantation. Case 2. A 21-year-old male was referred by general practitioner to our outpatient clinic for palpitations. Cardiovascular physical examination and ECG were normal with no evidence of arrhyhtmia or cardiac murmurs. Transthoracic echocardiography revealed central mild aortic valve regurgitation in a suspected quadricuspid aortic valve (i.e., an X-shaped commissure pattern during diastole and a rectangular appearance during systole in the parasternal short-axis view). Left ventricular size and function and ascending aorta dimensions were normal. There was no associated congenital cardiovascular abnormality. 3D-Transesophageal echocardiography confirmed the evidence of a quadricuspid aortic valve. The cusps appeared to be of different size: two equal larger cusps and two equal smaller cusps (Type C, Hurwitz and Robert's classification), thin and mobile. The patient was advised to echocardiographic follow-up at intervals of 12 months. Conclusions: We describe two cases of aortic valve congenital anomalies in two coetaneous patients with completely different impacts on hemodynamics. Severe aortic stenosis complicated unicuspid aortic valve whereas quadricuspid aortic valve was associated with mild aortic regurgitation. 3D-Transesophageal echocardiography was essential for accurate morphological characterization of the aortic valves.